Developing An Interactive Chemistry E-module Based on Problem-based Learning to Improve Critical Thinking Skills of High School Students - Asmi, Andalia; Silaban, Saronom; Silaban, Ramlan (Jurnal Paedagogy, 2024)
This study aims to develop an interactive chemistry E-module based on problem-based learning (PBL) to improve the critical thinking skills of high school students in class X and measure its feasibility. This research used the research and development method with the ADDIE model, which consists of 5 stages (Analysis, Design, Development, Implementation, and Evaluation). The tools used in this study were test tools and non-test tools, namely modified BSNP standard verification sheets and essay questions. The data analysis techniques used in this research were qualitative and quantitative. The results of the feasibility test from the materials specialist instructors, and chemistry teachers, as well as media specialists, an average result of 82.7% met the "very fair" criterion. An average result of 93.12% met the "highly feasible" criterion. Based on classroom learning experiments, the E-module can improve students' critical thinking skills by achieving an N gain value of 0.48 in the medium category. It was also evidence of a 55% increase in students' average critical thinking ability score using electronic modules and belonging to the critical category. When learning with the E module, a significant difference occurs at the significance level Î±=0.000.